“Dreamers Often Lie”: On “Compromise”, the subversive documentation of an Israeli- Palestinian political adaptation of Shakespeare’s Romeo and Juliet (Altre Modernità, 2010)
Is Romeo and Juliet relevant to a description of the Middle-East conflict? This is the question raised in Compromise, an Israeli documentary that follows the Jerusalem Khan Theater's production of the play in the mid-1990's. This paper describes how the cinematic documentation of a theatrical Shakespeare production can undermine the original intentions of its creators. This staging of the play was carefully planned in order to demonstrate to the country and the world that Israelis and Palestinians are willing to search for a peaceful solution in the Middle East: Two directors - Israeli -Eran Baniel and Palestinian Fuad Awad - co-directed both Israeli and Palestinian actors, using both languages: Arabic and Hebrew. This seemingly balanced solution was acclaimed on European television but for Israeli director Even, this was only a façade. Following backstage situation,  Compromise reveals the truth behind the mask in order to denounce the manipulative use of what Italian philosopher Giorgio Agamben defines as state of emergency, which is the hegemonic mechanism that deprives people of the elementary civil rights. Questioning the issue of co-existence against the political background of the 1990's (including bomb attacks and the signing of the Camp David Treaty in 1993), the film plays on the discrepancy between the denouement of Romeo and Juliet and the unsolvable situation in which people in the Middle-East - amongst them the actors themselves- are condemned to live.
Keywords: Romeo and Juliet; Middle East Conflict; Israeli documentary filmmaking; Georgio Agamben; State of Emergency